HUBUNGAN KEKUATAN OTOT LENGAN DAN KELENTUKAN PERGELANGAN TANGAN TERHADAP SERVIS ATAS PADA ATLET BOLAVOLI UNP - Muliyana, Nana; Mariati, Sari; Putra, Yogi Arnaldo; Rudyanto, Rudyanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to determine the relationship between arm muscle strength and wrist flexibility and the overhand service ability of volleyball athletes at Universitas Negeri Padang (UNP). A quantitative correlational research design was employed. The population consisted of 20 UNP volleyball athletes, with 17 athletes selected as the sample using purposive sampling. Arm muscle strength was measured using a one-minute push-up test, wrist flexibility was assessed with a goniometer, and overhand service ability was evaluated through six service attempts. Data were analyzed using the Pearson Product-Moment correlation and multiple correlation tests with SPSS version 32.0 at a significance level of 0.05. The results revealed that arm muscle strength (r = 0.966; p < 0.05) and wrist flexibility (r = 0.944; p < 0.05) each had a very strong relationship with overhand service ability. Moreover, both variables jointly demonstrated a very strong relationship with overhand service performance.